Lateral and Normal Capillary Force Evolution of a Reciprocating Liquid Bridge - Song, Qingrui (Langmuir : the ACS journal of surfaces and colloids, 2021)
Capillary forces of a shearing liquid bridge can significantly affect the friction and adhesion of interacting surfaces, but the underlying mechanisms remain unclear. We custom built a surface force apparatus (SFA, ±2 μN) equipped with in situ optical microscopy and performed normal and lateral force measurements on a reciprocating water bridge formed between two flat plates. A modified wedge method was developed to correct the unique force measurement errors caused by the changing bridge geometry and position. The results found (1) strong linear relations among the bridge shear displacement, the cosine difference between the left and right contact angles, and the lateral adhesion force and (2) the normal adhesion force increased monotonically up to 13% as the bridge geometry approached its axisymmetric state. Quasi-static force analyses based on a newly developed decahedral model showed good agreement with the experiments and improved accuracy compared with that of cylindrical or rectangular column models previously proposed in the literature. Although limited in certain aspects, this study may (1) prove helpful to the design and analysis of liquid bridge force experiments on platforms similar to the SFA used in this study and (2) help to bridge the gap between friction and liquid bridge physics in the literature